2019
DOI: 10.1002/ajum.12128
|View full text |Cite
|
Sign up to set email alerts
|

Point‐of‐care echocardiography – A road to future or a step backwards

Abstract: Echocardiography (Echo) has a myriad of clinical applications. Traditionally, it was performed and interpreted by cardiologist but the scope of its applications has lead physicians of other specialities to learn this useful skill. One of the newer and expanding scope of echocardiography is point-of-care (POC) echocardiography. In this review article, we aim to discuss the clinical applications of POC echo, common protocols and its limitations. Despite its widespread use, there is paucity of data describing its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Alongside complete echocardiographic examination, focused echocardiography protocols are being proposed to quickly assess hemodynamics in a variety of acute clinical settings. In critical care, FICE, RUSH and FATE are quite well-known [ 27 ]. Indeed, point-of-care ultrasound protocols have the advantage of being fast and, when used properly, they can give valuable information that can impact patient care.…”
Section: Discussionmentioning
confidence: 99%
“…Alongside complete echocardiographic examination, focused echocardiography protocols are being proposed to quickly assess hemodynamics in a variety of acute clinical settings. In critical care, FICE, RUSH and FATE are quite well-known [ 27 ]. Indeed, point-of-care ultrasound protocols have the advantage of being fast and, when used properly, they can give valuable information that can impact patient care.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of point of care ultrasound (POCUS) as a reliable bedside clinical tool that influences decision making and diagnosis provides timely intervention in the emergency department. 8 Several studies have suggested that the utility of POCUS in the emergency setting be a similar ability to detect cardiac pathology accurately compared to the conventional TTE. 9,10 However, the common prerequisite would be an experienced or trained operator of POCUS and the accessibility of the POCUS at the center.…”
Section: Discussionmentioning
confidence: 99%
“…shock that may be the cause of shock or hypotension [51]. TTE may be used to detect a possible cause of AHF and subsequently to initiate the appropriate treatment, and to optimize the previously initiated treatment.…”
Section: Cardiac Function Index (Cfi)mentioning
confidence: 99%
“…FATE is a protocol that enables a focused and systematic approach in critically ill patients, aiming to find a potentially reversible cause of haemodynamic instability, such as pulmonary embolism, cardiac tamponade, systolic heart failure, aortic dissection, hypovolaemic shock, obstructive shock, or distributive shock [ 49 , 50 ]. The FAST protocol is used to exclude tamponade in trauma patients when intra-abdominal or thoracic bleeding is suspected, whereas the RUSHed protocol is used to detect pathologies like tamponade, pneumo- and haemothorax, pulmonary embolism, aortic dissection, and cardiogenic shock that may be the cause of shock or hypotension [ 51 ]. TTE may be used to detect a possible cause of AHF and subsequently to initiate the appropriate treatment, and to optimize the previously initiated treatment.…”
Section: Echocardiographymentioning
confidence: 99%